Studi Komparasi Meja Resepsionis pada Hotel Mercure di Kota Bandung - Friana, Yuan Okta (Institut Teknologi Nasional, Bandung, 2025)
The lobby is the most important part of a hotel because the lobby can be the first impression when visitors first enter the hotel. The lobby can be the main focus of a hotel, namely providing the image and identity of the hotel and describing the condition of the hotel as a whole. The reception desk is the object most visited and seen by visitors when entering the hotel lobby area. The reception desk has many functions in the hotel lobby area, such as visitor administrative activities and receptionist activities in managing hotel data. Therefore, the reception desk is an important thing in a hotel. This time, research will be carried out on a comparative study of hotel reception desks at Mercure hotels in the city of Bandung by reviewing aspects of shape, color, material and ergonomics. The case studies used are the Grand Mercure Setiabudhi Bandung hotel, the Mercure Nexa Supratman Bandung hotel, and the Mercure City City Center Bandung hotel. This study used descriptive qualitative method. With this journal, it is hoped that readers will know more about the value of the aspects contained in hotel reception desks.Keywords: reception desk, shape, format, color, material, ergonomics.